2020
DOI: 10.1002/hbm.25011
|View full text |Cite
|
Sign up to set email alerts
|

From a deep learning model back to the brain—Identifying regional predictors and their relation to aging

Abstract: We present a Deep Learning framework for the prediction of chronological age from structural magnetic resonance imaging scans. Previous findings associate increased brain age with neurodegenerative diseases and higher mortality rates. However, the importance of brain age prediction goes beyond serving as biomarkers for neurological disorders. Specifically, utilizing convolutional neural network (CNN) analysis to identify brain regions contributing to the prediction can shed light on the complex multivariate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 72 publications
8
75
0
Order By: Relevance
“…These findings are particularly in agreement with studies describing the brain's fluid-filled ventricles as a biomarker of the aging brain ( 64 , 65 ). We found an high overlap with the regions identified in the work of ( 40 ). The authors used CNN models in conjunction with explainable AI techniques to derive explanation map which highlighted a major contribution of ventricles and cisterns.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…These findings are particularly in agreement with studies describing the brain's fluid-filled ventricles as a biomarker of the aging brain ( 64 , 65 ). We found an high overlap with the regions identified in the work of ( 40 ). The authors used CNN models in conjunction with explainable AI techniques to derive explanation map which highlighted a major contribution of ventricles and cisterns.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, we evaluated the ensemble variability as proposed in ( 40 ). This metric is assessed as the standard deviation of the prediction error within the ensemble and is related to the uncertainty in neural networks ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a Second, these methods can produce results that are independent of model and data, and thus inadequate for model debugging and inspection ( 28 ). Finally, additional techniques must be used for combining individual subject saliency maps of into population-level visualizations ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brain ageing study is a recent example of the predictive analysis paradigm (Brown et al, 2012; Cole et al, 2018, 2017; Cole and Franke, 2017; Dosenbach et al, 2010; Franke et al, 2010; Levakov et al, 2020; Neeb et al, 2006). Studies showed that individuals’ chronological age can be predicted accurately from brain MRI scans (Cole et al, 2017).…”
Section: Introductionmentioning
confidence: 99%